(untitled) (Revista Innova Educación, 2023)
The objective of the research was to characterize the learning styles that predominate in the technical high school students of the Oswaldo Guayasamín Educational Unit of the city of Santo Domingo, through the CHAEA Questionnaire for the improvement of their formative process. The methodology was non-experimental, descriptive, explanatory and field under a mixed research approach using for this purpose an internationally validated Instrument by the authors Honey and Alonso (2012), which was adapted to the Ecuadorian context through the opinion of 3 experts and a KR20 reliability of 0.80, the sample by convenience was applied to 174 students of first, second and third year of high school through Google Forms and the data were processed with the SPSS V.23 and Excel program. The results confirmed the moderate preference of the active style with 112 students; in consideration of gender, the male population has a preference for the active style (74), while the female population shares the same (38) but tends towards the pragmatic (36). In conclusion, the prevalence of the active learning style in technical education accompanied by the equipment for practices, complements student learning.